4 - Recreating African Futures through literary imagination. The newest gender, racial, national and African identities as revealed in Mario Lúcio Sousa’s O Novíssimo Testamento (The newest Testament) (Cape Verde) - Catarina Martins, (African Sociological Review, 2015)
The role of literature in imagining and building African identities, social roles, economic dynamics and political structures cannot be underestimated. Indeed, from anti-colonialism through the preand immediate post-independence periods up to the contemporary postcolonial state, literature has been path breaking: it was through literature that pre-existing realities and historical processes were critically revised in important ways. And it was also through literature that future projects were designed that inspired political agents of all sorts, the most important example being the very construction of African states as described by the poets and storytellers that were decisive in creating the “imagined communities” that would sustain political struggle.